Short range order and phase separation in Ti-Al alloys - Wood, H; Smith, G; Cerezo, A (1998)
The phase decomposition mechanism operating in binary Ti-Al alloys in the two phase alpha + alpha(2) region has been investigated. A Ti-15at.%Al alloy was aged in the range 450-750 degrees C for various time periods. The resulting microstructures were studied by transmission electron microscopy (TEM) and atom probe field ion microscopy (APFIM). Computer simulations of phase separation in this alloy were also carried out using a dynamic Ising model. Results from the computer simulations suggest decomposition occurs via a conditional spinodal route, whereby compositional phase separation is contingent upon prior ordering of the matrix. Experimental studies to date are fully consistent with this mechanism. (C) 1998 Elsevier Science S.A. All rights reserved.